Sperm swimming in the polychaete Galeolaria caespitosa shows substantial inter-individual variability in response to future ocean acidification - Schlegel, Peter; Havenhand, Jon N.; Obadia, Nicolas; Williamson, Jane E. (Marine Pollution Bulletin, 2014)
The rapidity of ocean acidification intensifies selection pressure for resilient phenotypes, particularly during sensitive early life stages. The scope for selection is greater in species with greater within-species variation in responses to changing environments, thus enhancing the potential for adaptation. We investigated among-male variation in sperm swimming responses (percent motility and swimming speeds) of the serpulid polychaete Galeolaria caespitosa to near- (δpH -0.3) and far-future ocean acidification (δpH -0.5). Responses of sperm swimming to acidification varied significantly among males and were overall negative. Robust sperm swimming behavior under near-future ocean acidification in some males may ameliorate climate change impacts, if traits associated with robustness are heritable, and thereby enhance the potential for adaptation to far-future conditions. Reduced sperm swimming in the majority of male G. caespitosa may decrease their fertilization success in a high CO 2 future ocean. Resultant changes in offspring production could affect recruitment success and population fitness downstream.